L’“Urban Digital Twin”, l’Incertezza e l’Osservazione della Terra: il Programma europeo Copernicus - Taramelli, Andrea; De Bernardinis, Bernardo; Castellani, Maria Vittoria; Farruggia, Sergio (GEOmedia, 2022)
The "digital twins" applied to cities and territories -as well as to their inhabitants- are already a reality and also at our disposal for the future. Therefore, being creators and/or beneficiaries of these artifacts, we all must learn to live with them. In fact, the increasing complexity of our living conditions and of the knowledge and technologies needed and used to deal with it, requires us to consider uncertainty unavoidable. We have to be aware of it and relate to it responsibly, particularly when we make use of the impressive amount of information that Earth Observation programs, such as Copernicus, produce and make available to us.